Neumonía bacteriana en paciente femenino de 63 años de edad. - Mayorga Córdova, Yuleidy Mabel (2020)
63-year-old female patient with bacterial pneumonia, hypertensive attends a medical consultation with symptoms of respiratory distress, frequent cough, fever, vomiting, decreased level of consciousness, chest pain, during her hospital stay she receives amoxicillin-clavulanic acid treatment 500/125 mg every 8 hours or 875/125 mg every 12 hours, Cefuroxime 500 mg every 12 hours or Levofloxacin 750 mg / day orally for 7-10 days and oxygen therapy rehabilitation therapies are applied. Bacterial pneumonia is a serious infection of the lungs that causes symptoms such as coughing up phlegm, fever and shortness of breath, arising from a cold or flu that does not heal or worsens over time, caused by the bacteria in Streptococci. pneumoniae, is common in elderly patients with comorbidities such as hypertension, heart failure and COPD, for which they are at higher risk. The objective of the clinical study was to observe the clinical manifestations and diagnosis of bacterial pneumonia, in order to carry out a correct clinical management, the important pathological aspects were studied, for the application of respiratory rehabilitation therapies and the administration of drugs, which will allow it to evolve in a timely manner to the patient.